Spiritual Practices and The Acquisition of ‘Ilm Ladunni at Pondok Pesantren Tauhid Al Bajuri: An Epistemological Perspective of Al-Ghazali - Rohman, Ahmad Yani Fathur; Huda, Muhammad Qomarul (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
This study examines the forms, meanings, and processes of spiritual practices in relation to the acquisition of ‘ilm ladunni (divinely bestowed knowledge) at Pondok Pesantren Tauhid Al Bajuri, and analyzes their relevance to Al-Ghazali’s epistemological framework. The study employs a qualitative approach with a phenomenological orientation to explore lived experiences and interpretations of spiritual practices within the pesantren context. Data were collected through participant observation, in-depth interviews with key participants, and documentation of institutional practices. The findings show that spiritual practices such as dhikr, khalwat, riyadhah, and tafakkur function as structured processes of self-discipline and inner purification. These practices are understood as preparatory stages for receiving knowledge, closely associated with the concept of tazkiyat al-nafs. The process of acquiring ‘ilm ladunni is interpreted as a gradual transformation involving stages of takhalli, tahalli, and tajalli, through which the heart (qalb) becomes receptive to deeper forms of understanding. The study further indicates that the distinction between ‘ilm kasbi and ‘ilm ladunni is reflected in practice as a complementary relationship rather than a dichotomy. Intellectual learning provides a conceptual foundation, while spiritual discipline contributes to the formation of inner readiness. These findings demonstrate that Al-Ghazali’s epistemological framework continues to operate within contemporary pesantren education, where knowledge is experienced as both learned and lived.